The fifth doctrine [large type] - Robards, Karen (The guardian series, 2019)
"It took one hell of an effort for the authorities to finally get the jump on master manipulator Bianca St. Ives, but now that they have, it's far from the capture she expected. Instead of taking her in, there's an offer on the table, a one-shot deal that would allow Bianca to walk away scot-free as if they'd never found her. And all she has to do is run one last mission--the kind she might never return from. But if Bianca wants to go back to her normal life in Savannah, it's not like she has a choice. An intelligence operation is already under way in North Korea, one that's poised to end the country's existing tyrannical regime for good. But first, the US need one of their own to go undercover as the female hacker who recently stole top secret intel from NORAD. Enter Bianca. After everything she's seen, Bianca knows feeding fake information directly into the belly of the beast is about as dangerous as it gets. It could mean torture or endless imprisonment--assuming she survives. But it might also ignite the kind of chaos that forces a revolution. It might just change the world. Besides, if Bianca has to go down, she's gonna go down swinging... This is part of "The Guardian" series."--